Penulisan Jurnal Ilmiah Berbasis Teknologi Digital untuk Meningkatkan Kompetensi Publikasi Mahasiswa - Noneng Marthiawati; Hetty Rohayani; Kevin Kurniawansyah; Jasmir Jasmir; Gustinar Gustinar (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
This community service activity was conducted at Universitas Muhammadiyah Jambi, involving students from the Information Systems study program as the primary participants. The main problems identified among participants included a limited understanding of the structure of scientific articles, inadequate paraphrasing skills, and a lack of competence in using reference management applications. In addition, the utilization of digital technology to support scientific writing was not yet optimal, despite the availability of adequate technological facilities. This activity aimed to improve students’ competencies in writing scientific articles in accordance with journal standards and to enhance their ability to utilize digital technology as a supporting tool for writing and publication. The method applied was a training-based approach combined with intensive mentoring. The training materials covered the structure of scientific articles, proper academic writing techniques, paraphrasing strategies to avoid plagiarism, the use of reference management tools, and the application of digital technology in scientific writing. The contribution of this activity lies in strengthening students’ practical academic skills while fostering a productive and technology-oriented academic culture. The results indicated a significant improvement in students’ understanding and skills. The average score increased from 54.25 in the pre-test to 79.63 in the post-test, representing a 46.78 percent improvement. Furthermore, most participants were able to independently produce draft scientific articles with a more systematic structure and effectively use reference management tools. The activity also contributed to increased motivation among students to write and publish scientific work.